Population and distribution of Javan langur (Trachypithecus auratus Geoffroy E. 1812) in Sokokembang Forest, Petungkriyono Sub-district, Pekalongan District, Central Java, Indonesia - INTAN RACHMADANTI AL-HUDA; IKE NURJUITA NAYASILANA; GALUH MASYITHOH; ARIF SETIAWAN (Society for Indonesian Biodiversity, 2024)
Abstract. Al-Huda IR, Nayasilana IN, Masyithoh G, Setiawan A. 2024. Population and distribution of Javan langur (Trachypithecus auratus Geoffroy E. 1812) in Sokokembang Forest, Petungkriyono Sub-district, Pekalongan District, Central Java, Indonesia. Biodiversitas 25: 1514-1520. Sokokembang is one of the potential habitats that provide a source of feed, means of movement, and shelter for Javan langurs (Trachypithecus auratus Geffroy E, 1812), which are one of the threatened Colobinae, the endemic primate of Java and Bali. Javan langur has been in decline for the last three generations. Javan langur conservation requires data and assessment of natural habitat distribution, size, and condition. This study aims to determine the population size and distribution pattern of Javan langurs in the Sokokembang forest, Central Java, Indonesia, which can be used as a basis for habitat management. The demography parameters used in this study were the population size, population density, age structure, and sex ratio. The study has been conducted from May to June 2023 on plots 18 to 21 of Sokokembang forest, Central Java. The study used the concentration count method and the nearest neighbor analysis using Arcmap 10.8. Eleven groups were identified, with the population size of each group ranging from 3 ± 23 individuals. The population density of Javan langurs was 7.46 individuals/km2. The age structure of Javan langurs in Sokokembang was dominated by the adult age class, and the male-to-female sex ratio was 1:3. The results showed a random distribution pattern of Javan langurs in the Sokokembang forest.